Effect of Mg doping in ZnO buffer layer on ZnO thin film devices for electronic applications. (May 2016) - Giri, Pushpa; Chakrabarti, P.
Abstract: Zinc Oxide (ZnO) thin films have been grown on p-silicon (Si) substrate using magnesium doped ZnO (Mg: ZnO) buffer layer by radio-frequency (RF) sputtering method. In this paper, we have optimized the concentration of Mg (0–5 atomic percent (at. %)) ZnO buffer layer to examine its effect on ZnO thin film based devices for electronic and optoelectronic applications. The crystalline nature, morphology and topography of the surface of the thin film have been characterized. The optical as well as electrical properties of the active ZnO film can be tailored by varying the concentration of Mg in the buffer layer. The crystallite size in the active ZnO thin film was found to increase with the Mg concentration in the buffer layer in the range of 0–3 at. % and subsequently decrease with increasing Mg atom concentration in the ZnO. The same was verified by the surface morphology and topography studies carried out with scanning electron microscope (SEM) and atomic electron microscopy (AFM) respectively. The reflectance in the visible region was measured to be less than 80% and found to decrease with increase in Mg concentration from 0 to 3 at. % in the buffer region. The optical bandgap was initially found to increase from 3.02 eV to 3.74 eV by increasing the Mg content from 0 to 3 at. % but subsequently decreases and drops down to 3.43 eV for a concentration of 5 at. %. The study of an Au:Pd/ZnO Schottky diode reveals that for optimum doping of the buffer layer the device exhibits superior rectifying behavior. The barrier height, ideality factor, rectification ratio, reverse saturation current and series resistance of the Schottky diode were extracted from the measured current voltage ( I – V ) characteristics.